2006
DOI: 10.1051/0004-6361:20064815
|View full text |Cite
|
Sign up to set email alerts
|

SiO and CH3CCH abundances and dust emission in high-mass star-forming cores

Abstract: Aims. We determine the fractional SiO abundance in high-mass star-forming cores, and investigate its dependence on physical conditions, to provide constraints on the chemistry models of the formation of SiO in the gas phase or via grain mantle evaporation. The work addresses also CH 3 CCH chemistry, as the kinetic temperature is determined using this molecule. Methods. We estimate the physical conditions of 15 high-mass star-forming cores and derive the fractional SiO and CH 3 CCH abundances using spectral lin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
51
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(79 citation statements)
references
References 79 publications
24
51
4
Order By: Relevance
“…1 apply here. represents an evolutionary line for molecular outflows driven by massive YSOs, compatible with the scenario proposed by Beuther & Shepherd (2005) in which initially well collimated outflows gradually disappear to make way for a wide-angle wind-dominated outflow. Our result is consistent with the findings of Miettinen et al (2006), who measured a decrease of the SiO abundance with core temperature in a sample of 15 UC Hii regions and concluded that SiO outflows are less frequent in more evolved, warmer cores. Given that our sample, which includes IR-dark sources, presumably covers a wider range of evolutionary phases, this represents the first time that clear evidence of a decrease in jet/outflow activity with time is found in a sample of high-mass SFRs.…”
Section: Decrease Of Sio Outflow Activity With Timesupporting
confidence: 93%
“…1 apply here. represents an evolutionary line for molecular outflows driven by massive YSOs, compatible with the scenario proposed by Beuther & Shepherd (2005) in which initially well collimated outflows gradually disappear to make way for a wide-angle wind-dominated outflow. Our result is consistent with the findings of Miettinen et al (2006), who measured a decrease of the SiO abundance with core temperature in a sample of 15 UC Hii regions and concluded that SiO outflows are less frequent in more evolved, warmer cores. Given that our sample, which includes IR-dark sources, presumably covers a wider range of evolutionary phases, this represents the first time that clear evidence of a decrease in jet/outflow activity with time is found in a sample of high-mass SFRs.…”
Section: Decrease Of Sio Outflow Activity With Timesupporting
confidence: 93%
“…Indeed, Sakai et al (2010) found a trend opposite to ours, and they proposed that the SiO emission from the mid-IR dark sources originates in newly formed shocks, while the SiO emission from more evolved, mid-IR bright sources could originate in gas that was shocked earlier in time. This could be related to the discovery by Miettinen et al (2006), namely that the SiO abundance in massive clumps appears to decrease as a function of gas kinetic temperature, which might reflect an evolutionary trend.…”
Section: Sio (Silicon Monoxide)mentioning
confidence: 63%
“…Faúndez et al (2004) reported a luminosity of 1.7 × 10 4 L obtained by integrating the spectral energy distribution and assuming d = 0.8 kpc. Distances between 700 pc and 2.2 kpc are reported in the literature (i.e., Miettinen et al 2006;Forster & Caswell 1989). However, the latter is based on maser emission lines.…”
Section: Introductionmentioning
confidence: 88%
“…However, the latter is based on maser emission lines. Using the rotation curve determined by Brand & Blitz (1993) and velocities based on thermal lines (Bronfman et al 1996;MacLeod et al 1998;Miettinen et al 2006;Leurini et al 2011), the kinematical distance of IRAS 17233 is constrained to ≤1 kpc. The far distance (∼15 kpc) is unlikely because of the source extremely bright continuum and line emission at practically all observed wavelengths, which would indicate exceedingly high luminosities if the source were at the far distance.…”
Section: Introductionmentioning
confidence: 99%